Towards a Collaborative Geographical Information System to Support Collective Decision Making for Urban Logistics Initiative - Guerlain, Cindy; Cortina, Stéphane; Renault, Samuel (Transportation research procedia (Online), 2016)
This paper describes how a Geographical Information System (GIS) applied to urban logistics can be used for modelling complex urban freight situations, such as those related to the ‘last mile deliveries’. It also highlights the fact that combining a GIS with tangible technologies enables creating a collaborative tool that can be used by a wide range of logistics stakeholders, even the non-specialists. It is explained how this collaborative GIS has been subject to experimenting in workshops related to urban logistics in European cities (London, Brussels and Luxembourg). The specific case study of Luxembourg is detailed. Finally, the paper stresses the key benefits of such a collaborative GIS, namely to foster discussions around specific topics and to make collective decisions.